1991
DOI: 10.3109/01460869109009041
|View full text |Cite
|
Sign up to set email alerts
|

Children's Ratings of Postoperative Pain Compared to Ratings by Nurses and Physicians

Abstract: Children's ratings of their postoperative pain were compared to nurses' and physicians' ratings of the children's postoperative pain. Children and adolescents were able to rate their pain using a visual analogue scale (VAS). Although there were differences between groups on their mean pain ratings, the ratings of the nurses and physicians correlated significantly with the children's pain ratings. Also, the correlation between nurses and physicians was highly significant, indicating that the use of a VAS may he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Pain measurements took place at 8.00, 12.00, and 18.00 h. Pain assessment was performed by the attending nurse using the Children's and Infant's Postoperative Pain Scale (CHIPPS) [14] in children younger than 4 years and the Smiley scale and Visual Analogue Scale (VAS) [15,16] in older children. The CHIPPS scale includes the assessment of pain during motion of the patient.…”
Section: Methodsmentioning
confidence: 99%
“…Pain measurements took place at 8.00, 12.00, and 18.00 h. Pain assessment was performed by the attending nurse using the Children's and Infant's Postoperative Pain Scale (CHIPPS) [14] in children younger than 4 years and the Smiley scale and Visual Analogue Scale (VAS) [15,16] in older children. The CHIPPS scale includes the assessment of pain during motion of the patient.…”
Section: Methodsmentioning
confidence: 99%
“…Personal data, medical history, and the intra-and postoperative course were documented. Pain was assessed by the attending nurse using the Children's and Infant's Postoperative Pain Scale (CHIPPS) [19] in children younger than 4 years and with the Smiley and visual analogue scale (VAS) [20,21] in older children. Pain assessment was performed without movement the evening after the operation and the morning of the first and second postoperative days.…”
Section: Methodsmentioning
confidence: 99%
“…Of the 10 studies that documented or compared pain assessments made by both physicians and nurses of the same patients [26,[39][40][41][42][43][44][45][46][47], only one study reported a significant difference in pain assessment accuracy by provider type [46]. Sjöström et al [46] found that of the nurses and physicians that were less experienced (< 4 years of clinical experience), physicians showed good pain assessment accuracy while nurses showed only moderate pain assessment accuracy.…”
Section: Provider Typementioning
confidence: 96%